Question & Answer Session - NUNIS, Sadie-Jane (Institutional Knowledge at Singapore Management University, 2020)
Moderated by Ms Sadie-Jane Nunis, Head Librarian - Singapore Institute of Management (SIM) Library, and Vice-President - Library Association of Singapore (LAS).